Outcomes of microsurgical clipping vs coil embolization for ruptured aneurysmal subarachnoid hemorrhage: A multicenter real-world analysis of 583 patients in China. Issue 33 (August 2019) - Wang, Hong-Yu; Song, Jian; Gao, Fei; Duan, Xu-Dong; Gao, Xuan; Wang, Yuan; Cheng, Hong-Bo; Nan, Cheng-Rui; Zhao, Di
Abstract : Abstract: Aneurysmal subarachnoid hemorrhage (SAH) is a complex neurovascular syndrome with high disability and mortality. SAH patients may be managed with surgical clipping or coil embolization. In this study, we provided a real-world analysis of the outcome and prognostic factors of aneurysmal SAH in patients treated with coil embolization or microsurgical clipping. We retrospectively analyzed the medical records of aneurysmal SAH patients (n = 583) who underwent treatment at the First Hospital and the Second Hospital of Hebei Medical University, and Tangshan Worker's Hospital in China. All patients were evaluated by a combined neurosurgery and interventional neuroradiology team. Microsurgical aneurysmal clipping was performed using the skull base approach, while coil embolization was performed with bare platinum coils (with or without balloon assistance). The primary outcome was the Glasgow Outcome Scale (GOS) score at discharge. A total of 583 patients were included in this study, of which 397 (68.1%) of them underwent clipping and 186 (31.9%) received coil embolization. The patient cohort consisted of both poor grade and good grade aneurysmal SAH: 441 (75.6%) patients had good-grade (Hunt and Hess grade II or III) and 142 (24.4%) had poor grade (Hunt and Hess grade IV or V). Overall, 123 (21%) patients had unfavorable neurologic outcome (GOS score 1–3) and 460 (78.9%) patients had favorable neurologic outcome (GOS score 4 or 5). The mean GOS score at discharge was comparable for patients who underwent clipping and those received coil embolization ( P > .05). Multivariate analysis showed that clipping only [OR (95%CI): 0.03 (0.01, 0.36); P = .000] and clipping with CSF drainage [OR (95%CI): 0.41 (0.18, 0.89); P = .001] were independent factors of a favorable outcome in patients with aneurysmal SAH. Coil embolization with hematoma removal [OR (95%CI): 0.03 (0.01, 0.36); P = .000] was also an independent determinant of a favorable outcome. High baseline Fisher grades were associated with significantly increased risk of an unfavorable outcome [OR (95%CI): 2.08 (1.30, 3.33); P = .002]. Our findings suggested that both coil embolization and microsurgical clipping are viable treatment options for aneurysmal SAH patients. Procedures, such as CSF drainage and hematoma removal, performed in parallel with coil embolization and chipping should be considered when treating individual patients.